The ethnographic descriptions of Indonesian domestic workers in selected Malaysian middle class homes : case study in Klang, Selangor - Aananthi Thuraisamy, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Migrant workers began flooding the labour market of the country since the Malaysian economy achieved rapid growth rates, particularly in the late 1980s. The transition of change towards becoming an industrial country has also changed the family system in Malaysia. These changes have led to a new pattern of life among women to go out to work. This increased female participation in the workforce together with the expansion of the middle class households, led to an immediately heightened demand for migrant domestic workers in Malaysia towards the end of 20th century. Most of the demand for live-in maids is being met from neighbouring Indonesia. Though maids are foreigners and considered as strangers, they are accepted as a part of the households by the host families. Naturally, these maids bring along their cultural values, norms and beliefs into the Malaysian homes of different ethnicities. In the process of communication and interaction, they will experience cultural differences. Therefore, it is the intention of this paper to highlight the cross-cultural experiences of Indonesian maids as well as the host families in the process of adaptation within the households specifically in the aspect of cooking and food preparation. Fifteen local families who employed Indonesian maids in their homes were interviewed intensively to obtain responses for this study. In this paper, the researcher hopes to provide insights that both the employers’ families and their maids do influence each other culturally within the household context which lead to different degree of social adjustment process and eventually establish various patterns of cross cultural relationship between them.